Toe-brachial index and exercise test can improve the exploration of peripheral artery disease. (February 2018) - Kovacs, David; Csiszar, Beata; Biro, Katalin; Koltai, Katalin; Endrei, Dora; Juricskay, Istvan; Sandor, Barbara; Praksch, Dora; Toth, Kalman; Kesmarky, Gabor
Abstract: Background and aims: We assumed that hand-held Doppler ultrasound (DUS) at rest was insufficient to assess the severity of peripheral artery disease (PAD). Toe pressure and transcutaneous tissue oxygen pressure were studied to prove whether these could identify more patients with severe lower limb ischemia; exercise was applied to provoke ischemia. Methods: 120 patients with PAD and 30 volunteers without PAD were recruited. DUS, transcutaneous tissue oxygen pressure (tcpO2 ) and toe pressure measurements were performed at rest and after exercise. The differential power of these examinations for severe limb ischemia (SLI) was determined by receiver-operating curves (ROCs) and pattern recognition by independent multicategory analysis (PRIMA). Results: There was an obvious significant difference between the patient and control groups at rest; after exercise; the ratio of severely impaired values (ankle-brachial index – ABI, toe-brachial index – TBI, tcpO2 measured on index forefoot) increased significantly in the patient group ( p < 0.05). TBI, tcpO2, ABI measured after exercise could differentiate SLI better than the values of these tests at rest ( p < 0.001). In ROC analysis, the largest area under the curve (AUC) was covered by post- (AUC: 0.860) and pre-exercise TBI (AUC: 0.785), and post-exercise tcpO2 (AUC: 0.720) ( p < 0.001). Post-exercise TBI gained the best discriminant score in PRIMA. Conclusions: Pre- and post-exercise non-invasive vascular tests could reveal severe limb ischemia. Toe pressure measurement and TBI should become a basic part of the vascular workup. Highlights: The non-invasive vascular tests are able to detect lower limb ischemia. Post-exercise toe-brachial index could identify patients with severe limb ischemia. The tests can differentiate arterial and non-arterial origin of lower limb pain. Exercise testing and toe-brachial index should become routine procedures in vascular medicine.